EFFECT OF GARLIC PEEL EXTRACT (Allium sativum) ON THE PERFORMANCE OF BROILER - I G. H., Winoto; Dewi, G. A. M. K.; Wijana, I W. (Jurnal Peternakan Tropika; Vol 11 No 1 (2023): Vol. 11 No. 1 Tahun 2023; January - april, 2023)
This study aims to determine the effect of garlic peel extract (Allium sativum) on the performance of broilers aged 4 weeks. The research was conducted in Banjar Selanbawak Kelod, Selanbawak Village, Marga District, Tabanan Regency, Bali for 4 weeks. The design used was a completely randomized design with 4 treatments and 4 replications each using 5 chickens so that the total number of chickens used was 80 chickens. The treatment of this research was given through drinking water with each P0 without garlic peel extract (Control), P1 drinking water containing 1% garlic peel extract, P2 drinking water containing 2% garlic peel extract and P3 drinking water containing 3% extract garlic peel. The variables observed were ration consumption, drinking water consumption, final body weight, weight gain and FCR. The results showed that the P1, P2 and P3 treatments on ration consumption, drinking water consumption, final body weight, weight gain and FCR had no significant effect (P>0.05). Based on the results of the study it can be concluded that the giving of 1%, 2% and 3% extract of garlic peel (Allium sativum) has not been able to improve the performance of broilers aged 4 weeks. Keywords: chicken, garlic skin extract, chicken performance